2020
DOI: 10.1016/j.fertnstert.2020.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Exposure to Fine Inhalable Particulate Matter (PM2.5) on Sperm Functional Quality of Mice

Abstract: 0, p¼0.027). There were no significant influences of other investigated maternal lifestyle factors on oocyte dimorphisms.CONCLUSIONS: Cigarette smoking and the consumption of refined sugar appear to reduce oocyte quality. Therefore, it would be wise to advise female partners undergoing assisted reproduction treatments to abstain from smoking and consuming sugar to avoid decreased in vitro reproduction outcomes.SUPPORT: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of cluster analysis showed that the research directions of environmental and health management could be divided into seven different categories: soil pollution and health [3][4][5][6], water pollution and health [7][8][9][10][11], air pollution and health [12][13][14][15], food, medicine and health [16][17][18][19][20], indoor environment and health [21][22][23][24][25], urban environment and health [26][27][28][29][30], and environmental governance and health [31][32][33]. The research hotspots and frontiers in the field of environmental health problems mainly focused on indoor air pollution and control [34][35][36][37][38][39][40], treatment of schistosomiasis and veterinary drug residues [41][42][43][44][45][46], control and treatment of inhalable particulate matter in the atmosphere [47][48][49], monitori...…”
Section: Introductionmentioning
confidence: 99%
“…The results of cluster analysis showed that the research directions of environmental and health management could be divided into seven different categories: soil pollution and health [3][4][5][6], water pollution and health [7][8][9][10][11], air pollution and health [12][13][14][15], food, medicine and health [16][17][18][19][20], indoor environment and health [21][22][23][24][25], urban environment and health [26][27][28][29][30], and environmental governance and health [31][32][33]. The research hotspots and frontiers in the field of environmental health problems mainly focused on indoor air pollution and control [34][35][36][37][38][39][40], treatment of schistosomiasis and veterinary drug residues [41][42][43][44][45][46], control and treatment of inhalable particulate matter in the atmosphere [47][48][49], monitori...…”
Section: Introductionmentioning
confidence: 99%